Evaluation of the Pit Changes Introduced in 2022 as Part of the “Polish Deal” - Deresz Agnieszka Ewa; Podstawka Marian Grzegorz (Studia Ekonomiczne i Regionalne, 2024)
The subject of this paper is to evaluate the ‘Polish Deal’ programme introduced in 2022 in the tax area. The purpose of this article is to show the impact of the ‘Polish Deal’ legislation on net salaries of persons employed under an employment contract.